PRODUCT PLACEMENT DALAM FILM “SURGA YANG TAK DIRINDUKAN” - Salsabela, Fikha Ilmadina (Institut Seni Budaya Indonesia Bandung, 2017)
The development of communication media today, widely used by entrepreneurs to promote their products. One of the attractive promotional alternatives is to place ads on a film. Movies are able to convey an information and persuade an audience, so advertisers use the film as a promotional medium. This paper aims to convey the results of an analysis of product placement in the film. The object of this research are some products, namely beauty care hand body from Citra brand, Zalora's online shopping app and Biolysin's children's medicine promoted in the film in the movie of